1980
DOI: 10.1001/jama.1980.03310100025022
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass in Lifetime Tennis Athletes

Abstract: The effects of physical exercise on the status of bone mineralization for a population of lifetime athletes were investigated. The bone mineral content of the radii of experienced male tennis players was measured. The bone mass of the radius of the playing arm (mean, 1.37 g/cm) was greater than that of the nonplaying arm (mean, 1.23 g/cm) in all but one person. The results were compared with data for a nonathletic (normal) population. The quantity of bone mineral present in the playing arms of the athletic pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
4

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(71 citation statements)
references
References 9 publications
2
65
0
4
Order By: Relevance
“…Our results as well as those of others [27][28][29][30] emphasize the idea that muscles attached to sites of bone density measurements directly influence those BMD values. Rugby, bodybuilding and fighting sports resulted in a significantly higher spine BMD.…”
Section: Discussionsupporting
confidence: 87%
“…Our results as well as those of others [27][28][29][30] emphasize the idea that muscles attached to sites of bone density measurements directly influence those BMD values. Rugby, bodybuilding and fighting sports resulted in a significantly higher spine BMD.…”
Section: Discussionsupporting
confidence: 87%
“…These studies have shown differences in appendicular bone mass of as much as 25% between affected and unaffected limbs. The converse of this is found in athletes who use their limbs asymmetrically in sporting activity, for example tennis players, who have substantially greater bone mineral content in the serving forearm than in the contralateral forearm [15].…”
Section: Discussionmentioning
confidence: 97%
“…Evidence demonstrating the importance of exercise for the skeleton comes from immobilization and bedrest studies [21,22], cross-sectional studies showing that physically active subjects have significant higher BMD than age-matched sedentary controls [for overview see, for example, 18,[23][24][25], and within-subject studies indicating that athletes have greater bone mass in their dominant playing extremity than in their nondominant one [26,27]. The only study design that allows causal inferences, however, is the controlled intervention trial, especially when the groups are formed by randomization.…”
Section: Introductionmentioning
confidence: 99%